Online course on vaccinating people with HIV/AIDS - effectiveness in the knowledge of nursing professionals - Larissa Gerin; Elucir Gir; Lis Aparecida de Souza Neves; Luzia Márcia Romanholi Passos; Renato de Ávila Kfouri; Renata Karina Reis (Universidade de São Paulo, 2024)
Abstract Objective: analyzing the effectiveness of an educational intervention on the knowledge of nursing professionals regarding the immunization of people with the human immunodeficiency virus. Method: a quasi-experimental study evaluated professionals' knowledge through a knowledge test applied before and after the development of an online training course. The data was analyzed using frequency, median, mean, standard deviation, and association tests. Results: the sample consisted of 77 nursing professionals whose mean age was 43.2 years (SD+/-8.2). More than half of the individuals worked in basic health units (58.4%), 22.1% worked in specialized services that provide clinical monitoring for people with the human immunodeficiency virus, and 42 (54.5%) were nursing assistants or technicians. The professionals' performance improved after the intervention, with an increase in the median number of correct answers from 23.0 to 27.0 (p<0.001). Conclusion: offering an online training course on the immunization of people with the human immunodeficiency virus, as a continuing education activity, proved to be effective in improving nursing professionals' knowledge on this subject.